Evaluación de dos protocolos de sincronización de receptoras de embriones bovinos utilizando dosis de Cipionato de estradiol en diferentes edades y raza - Delgado Montalván, Jonathan Rubén (2025)
The objective was to evaluate two estrus synchronization protocols in embryo recipient Brangus cows using estradiol cypionate (ECP) doses. And to know if it influences estrus presentation, corpus luteum and corpus luteum size and also the cost of these protocols. The present investigation was carried out at the Fortuna ranch in the province of El Oro using a total of 70 cows, cyclic cows, with a good state of health at the general clinical examination, with a body condition of 2.5 to 3.5 and with more than one calving. The animals were distributed in two groups by treatments: first group = T1 was used 1 ml of estradiol cypionate and the second group = T2 was used 2 ml of estradiol cypionate. The evaluation of the rate of estrus presentation was carried out, and the presence of the corpus luteum (CL) and its size at day 18 after the beginning of estrus synchronization was observed by means of the ultrasound scanner. Based on the symptoms presented by the cows in heat, 77.14% (27/35) in T1 and 80% (28/35) in T2. In the presence of CL, the same percentage of those that were observed in estrus was achieved. The measurement of the CL of those animals that were present was classified in 4 groups, where both T1 and T2 reached a higher percentage in grade 1 with 55.6% (15/27) and 60.71% (17/28) and a lower value in the same way in the two treatments of 11.1% (3/27) and 7.14% (2/28) in grade 4. 75 and the T2 value per cow was 8.65 and for the whole group was 302.75, concluding that there was no statistically significant difference (p> 0.05), however.